Genotypic variations of Porphyromonas gingivalis in chronic periodontitis patients with and without diabetes: An in vitro study using arbitrarily primed-polymerase chain reaction and heteroduplex-polymerase chain reaction - Siladitya Sen; Kukkamalla Meena Anand (Wolters Kluwer Medknow Publications, 2019)
Context: Diabetes has become an endemic throughout the world. Periodontitis is associated with diabetes, and it has been regarded as the sixth complication of diabetes. However, the role of diabetes on periodontopathic microbiota such as Porphyromonas gingivalis remains unclear. Aims: To compare the total number of different genotypes of P. gingivalis in chronic periodontitis patients with and without diabetes by using arbitrarily primed-polymerase chain reaction (AP-PCR) and heteroduplex-PCR. Settings and Design: This is a single-center comparative study. Materials and Methods: A total of 100 patients were included in this study. Patients were divided into two groups: Group A - patients having chronic periodontitis without diabetes (50) and Group B - patients having chronic periodontitis with diabetes (50). Subgingival plaque samples were collected from both groups of patients. Plaque samples were cultured for P. gingivalis. Positive culture samples and extracted DNA from samples by proteinase-K method were collected. Part of DNA samples were checked by AP-PCR using OPA-13 primer, and part of the DNA were checked using heteroduplex-PCR using P. gingivalis-specific Pg8 primer. Results were analyzed by polyacrylamide gel electrophoresis procedure. Statistical Analysis Used: Independent t-test and Chi-square test (SPSS 16) were used. Results: Thirty-four out of fifty samples of Group B patients were found positive for P. gingivalis, whereas 21 out of 50 samples in Group A were found positive for P. gingivalis. AP-PCR showed nine different genotypes in Group B and six different genotypes in Group A. Heteroduplex-PCR showed a total of seven different genotypes in Group B and five different genotypes in Group A. Conclusions: Results of this study show that, in diabetic condition, P. gingivalis shows increased variations in genotypes.